Towards Aesthetic-Oriented Teaching: A Structural Framework and Enhancement Approaches for Teachers' Aesthetic Education Competency in Primary and Secondary Schools - HE Xi; LIU Yuanzhen; BIAN Hanyan (Jiaoshi jiaoyu xuebao)
Teachers' professional competency, as the foundation and fundamental pursuit of a high-quality teacher workforce in the new era, is a core engine driving educational advancement. The Ministry of Education issued a document on "Comprehensively Implementing School Aesthetic Education Infiltration Action", which explicitly mandates that teachers should be infiltrated with aesthetic education, enhancing teachers' awareness and competency in aesthetic education across all disciplines. Teachers' aesthetic education competency guarantees the high-quality development of aesthetic education and puts forward new requirements for teachers. Serving as an essential professional competency for teachers in the new era, teachers' aesthetic education competency holds significant implications for inheriting the Chinese aesthetic spirit, resolving challenges in school aesthetic education, and guiding teachers towards aesthetic teaching. This paper constructs a framework of teachers' aesthetic education competency from the three dimensions of "affection, knowledge, and ability". To foster these dimensions, it is recommended to construct an environment conducive to the development of aesthetic education literacy, optimize the pre-service aesthetic education curriculum, develop specialized training programs integrating intelligent media into aesthetic education and establish interdisciplinary aesthetic education research platforms. These coordinated measures aim to provide comprehensive faculty support for advancing aesthetic education in primary and secondary schools.